Literature Review: Identification of Microplastics In Tropical Marine Fish - Ferry Cahya Raharja; Suryanti, Ani; Zainuddin, Muhammad; Sari, Lilik Kartika (AQUACOASTMARINE: Journal of Aquatic and Fisheries Sciences, 2025)
Microplastics are small plastic particles that measure no more than 5mm, formed through the fragmentation of larger plastic materials. Their presence in marine environments has become a global concern due to their potential to threaten biodiversity and ecosystem stability. In fish organisms, exposure to microplastics can cause various disturbances, including physiological changes, reduced growth rates, and damage to the digestive system. Microplastics have a significant impact on marine food webs, affecting organisms across various trophic levels, starting from plankton at the base of the food chain to apex predators such as marine mammals. The accumulation of microplastics in marine organisms can reduce their ability to survive and reproduce, leading to population instability and disrupting ecosystem balance. To address this issue, an integrated approach is needed, involving technological innovation, strengthening waste management systems, and improving public education. Additionally, implementing effective regulations and conservation and protection programs is crucial for ensuring the sustainability of marine ecosystems. Addressing this problem requires a comprehensive strategy, including technological innovation, waste management improvements, and public education. Regulatory measures and conservation efforts are also essential for the long-term sustainability of marine ecosystems. Keywords: Fish; Ecosystem; Bioaccumulation; Pollution; Biodiversity; Regulation